Social justice and social media: How medical schools display critical consciousness online. - Eray Yilmaz; Keegan D'Mello; Amrit Kirpalani (PLOS Digital Health)
Academic medical institutions have a pivotal role in addressing the inequalities faced by marginalized populations, especially by promoting values of social justice on online platforms that not only reach the medical sphere, but also the broader public. Central to this transformative agenda is the framework of critical consciousness (CC), which compels individuals to develop an acute awareness of societal inequalities and power dynamics and act as agents of change against inequalities across society. To investigate if and how medical schools use X (formerly Twitter) to display CC, tweets from March 22 - June 22, 2023 from all available Canadian medical school Twitter accounts were obtained and deductively coded. First, a content analysis was performed to collate and categorize tweets related to CC, followed by a critical discourse analysis with a CC framework to examine the role of language in conveying messages about equity and medical education. Of the 3442 tweets reviewed, 554 displayed CC (16.12%). The content analysis revealed that Empowerment of Marginalized Populations was the most prominent display of CC amongst tweets (n = 286), whereas there was a paucity of messaging around Intersectionality (n = 20). The critical discourse analysis revealed that language was purposefully used to positively spotlight equity-deserving individuals (e.g., "celebrate" and "recognize") with minimal dialogue framing institutions as agents of systemic power differentials. Medical schools ultimately advocate for positive change by sharing awareness-raising content that celebrate marginalized communities. However, the step beyond surface-level awareness-raising content towards critical self-reflection that acknowledged institutions' roles in perpetuating inequities was largely limited; this represents a missed opportunity to leverage the power of social media and engage in meaningful dialogue online to build trust between the healthcare sector and the public.